Isolation of Pleurotus florida derived acetylcholinesterase inhibitor for the treatment of cognitive dysfunction in mice - Kudrat Randhawa; Varinder Singh; Sanimardeep Kaur; Ravinder Kaur; Suresh Kumar; Richa Shri (Food Science and Human Wellness)
Our earlier work showed that hydromethanol extract (HME) of Pleurotus florida had antioxidant and anti-cholinesterase potential. This study aimed at isolating the constituent responsible for the activities. HME was subjected to bioactivity guided fractionation using in vitro anti-acetylcholinesterase (Ellman method) and antioxidant (DPPH scavenging assay). The most active constituent was evaluated in vivo employing i.c.v. streptozotocin (STZ) induced dementia in mice. Morris water maze test was used for evaluating memory, followed by biochemical estimations and histopathological studies. Bioactivity guided fractionation resulted in isolation of resveratrol (identified by IR, NMR and MS) and its content in P. florida fruiting bodies was 0.0098% (m/m, by a validated TLC densitometric method). It improved STZ induced dementia and neurodegeneration in mice by reducing brain acetylcholinesterase action and oxidative stress. The observed effects might be the presence of resveratrol. Our results further endorse that P. florida derived resveratrol can be a promising therapy for Alzheimer's disease.